The Effect Of Growth, Profitability And Liquidity To Bond Rating Of The Banking Firms Listed On The Indonesian Stock Exchange (Period 2009-2013) - Syamsu Rizal; Winda Sutanti (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
This study aims to identify and analyze the effects of growth, profitability and liquidity on bond ratings of the banking firms listed on the Indonesia Stock Exchange (Period 2009-2013). Measurement of growth using sales growth and Earnings per Share growth, profitability is measured by Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), while liquidity is measured by the Loan to Deposit Ratio (LDR). The sample in this study is the banking firms listed in Indonesia Stock Exchange 2009-2013 and ranked by PT. PEFINDO. Sampling using purposive sampling in order to obtain a total sample of 7 banking firms that meet the criteria of the study sample set. The technique of the data analysis in this study is using ordinal regression with SPSS 18.0 for Windows.The results showed that growth with sales growth of measurement has a positive influence on bond ratings while EPS growth measurement has no effect on bond ratings. Profitability with NPM and measurement ROA has a positive influence on bond ratings, when using ROE measurement has a negative influence on bond ratings. Liquidity with LDR of measurement has no effect on bond ratings.